2013
DOI: 10.1371/journal.pone.0065077
|View full text |Cite
|
Sign up to set email alerts
|

Association between Provider Volume and Healthcare Expenditures of Patients with Oral Cancer in Taiwan: A Population-Based Study

Abstract: BackgroundOral cancer requires considerable utilization of healthcare services. Wide resection of the tumor and reconstruction with free flap are widely used. Due to high recurrence rate, close follow-up is mandatory. This study was conducted to explore the relationship between the healthcare expenditure of oncological surgery and one-year follow up and provider volume.MethodsFrom the National Health Insurance Research Database published by the Taiwanese National Health Research Institute, the authors selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In the aging Taiwan society, there is also an increasing number of individuals dying of cancer who are covered by the national health insurance (NHI) system. Approximately 29,000 Taiwanese people died from cancer in 1997, and this increased to 40,300 in 2007, which accounted for 13 percent of deaths attributable to cancer [ 2 , 3 ]. There is a growing appreciation of cancer patients’ needs for end-of-life (EOL) care services, especially for those with terminal illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…In the aging Taiwan society, there is also an increasing number of individuals dying of cancer who are covered by the national health insurance (NHI) system. Approximately 29,000 Taiwanese people died from cancer in 1997, and this increased to 40,300 in 2007, which accounted for 13 percent of deaths attributable to cancer [ 2 , 3 ]. There is a growing appreciation of cancer patients’ needs for end-of-life (EOL) care services, especially for those with terminal illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…; Chen et al . 2013a,b). Medical centre physicians with well‐trained staff could perform treatment with a shortened operation period, appropriate antimicrobials and procedures, and well‐designed discharge planning, thereby resulting in fewer complications, shorter hospital stays, lower mortality rates and lower medical expenses (Halm et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Chen et al . 2013a,b). This observation is consistent with a previous study projected that asserts that medical centres could have improved care organisation and best‐practice protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goodness of fit between the association of the end-of-life expenditures and explanatory variables by multiple linear regression was assessed with residual analysis, and we found that it was not suitable for implementing multiple linear regression due to unequal variance assumption ( S1 Fig ). Considering the clustering effect of physician compensation, procedures and policy in each hospital ( S2 Fig ), the impact of each variable on medical cost was examined by hierarchical generalized linear model using a hospital-level random-intercept model [ 11 13 ]. A two-tailed value of p<0.05 was considered significant.…”
Section: Methodsmentioning
confidence: 99%